2000
DOI: 10.1161/01.hyp.35.5.1119
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Natriuretic Peptide Modifies Arterial Blood Pressure Through Nitric Oxide Pathway in Rats

Abstract: Abstract-The aim of the present study was to determine the relationship between the hypotensive effect of the atrial natriuretic peptide (ANP) and the nitric oxide (NO) pathway. N G -nitro-L-arginine methyl ester bolus (L-NAME, 1 mg/kg) reverted the decrease in mean arterial pressure induced by ANP administration (5 g/kg bolus and 0.2 g ⅐ kg Ϫ1 ⅐ min Ϫ1 infusion), and the injection of L-NAME before peptide administration suppressed the ANP hypotensive response. To confirm these findings, a histochemical reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…NOS blockade blunted the ANP hypotensive effect in both groups, but L-NAME treatment had a more marked impact on normotensive ones. These results confirm our previous findings indicating that the NO system is involved in the hypotensive effect induced by ANP and that this response is impaired in hypertensive animals (6,9). Thus our results suggest that ANP's hypotensive effects involve different mechanisms in SHR and in WKY, indicating that the NO system plays a more Table 4 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…NOS blockade blunted the ANP hypotensive effect in both groups, but L-NAME treatment had a more marked impact on normotensive ones. These results confirm our previous findings indicating that the NO system is involved in the hypotensive effect induced by ANP and that this response is impaired in hypertensive animals (6,9). Thus our results suggest that ANP's hypotensive effects involve different mechanisms in SHR and in WKY, indicating that the NO system plays a more Table 4 …”
Section: Discussionsupporting
confidence: 91%
“…In previous studies, we have demonstrated that ANP exerts its hypotensive, natriuretic, and diuretic effects, at least in part, through activation of cardiovascular and renal NOS (7,9). Furthermore, we have reported that the NPR-C natriuretic receptor mediates activation of NOS by ANP in the kidney (4,11).…”
mentioning
confidence: 99%
“…Accordingly, a recent study showed that ANP enhances NOS activity and NO production, suggesting that the NO pathway may be a second messenger for ANP. 41 The observed altered vascular responses could be related not only to a reduced production of NO but also to an altered responsiveness of VSMCs to NO due to an impaired activation of second messengers such as cGMP. 8 However, we found that basal cGMP levels were slightly increased in mesenteric arteries of DS rats on a high-salt diet, demonstrating that impaired endothelial function is not related to the altered VSMC reactivity to NO.…”
Section: D'uscio Et Al Salt Hypertension and Nep/ace Inhibitionmentioning
confidence: 97%
“…Differences in plasma ANP levels in the omapatrilat and captopril groups may help improve endotheliumdependent relaxations. Accordingly, a recent study showed that ANP enhances NO synthesis capability and NO production in endothelial cells, suggesting that the L-arginine-NO pathway may be a second messenger for ANP [82]. However, either omapatrilat or captopril normalized decreased eNOS protein expression as well as total NO 3 /NO 2 levels to a similar degree in the aortas of Dahl rats with salt-induced hypertension [50].…”
Section: Endothelial Function and Bradykinin Metabolismmentioning
confidence: 97%